2021
DOI: 10.3390/molecules26020295
|View full text |Cite
|
Sign up to set email alerts
|

Peretinoin, an Acyclic Retinoid, for the Secondary Prevention of Hepatocellular Carcinoma

Abstract: The high rates of hepatocellular carcinoma (HCC) recurrence after initially successful curative therapy emphasize ongoing unmet needs to prevent or reduce HCC recurrence. Retinoid acid (RA), a metabolite of vitamin A and its related analogues (termed retinoids) has been suggested as a promising chemotherapeutic agent in cancer treatment. The synthetic oral retinoid peretinoin is the only agent for the secondary chemoprevention of HCC after curative therapy that is currently well applied into clinical developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Recently, researchers reported that sulfarotene (WYC-209), an acyclic retinoid, overcame HCC resistance in a subset of cancer cells that were responsible for drug resistance (i.e., tumor-repopulating cells), possibly via RARα [ 217 ]. A promising retinoid at present for the prevention of HCC recurrence is peretinoin (NIK-333) [ 218 , 219 ], which is in clinical trials that are discussed in a separate review [ 220 ]. Pre-clinical studies showed that peretinoin suppressed steatosis and tumorigenesis in a mouse model of diet-induced NASH and HCC by promoting autophagy and inhibiting pro-inflammatory pathways [ 221 ].…”
Section: Retinoids In Liver Cancermentioning
confidence: 99%
“…Recently, researchers reported that sulfarotene (WYC-209), an acyclic retinoid, overcame HCC resistance in a subset of cancer cells that were responsible for drug resistance (i.e., tumor-repopulating cells), possibly via RARα [ 217 ]. A promising retinoid at present for the prevention of HCC recurrence is peretinoin (NIK-333) [ 218 , 219 ], which is in clinical trials that are discussed in a separate review [ 220 ]. Pre-clinical studies showed that peretinoin suppressed steatosis and tumorigenesis in a mouse model of diet-induced NASH and HCC by promoting autophagy and inhibiting pro-inflammatory pathways [ 221 ].…”
Section: Retinoids In Liver Cancermentioning
confidence: 99%
“…Since the structure of compound 5 possesses both an indole and retinoid group, understanding the biological activities of these substituents is also important. ATRA and its derivatives have been used to suppress the proliferation of various types of cancers [32][33][34] especially AML [35]. The effects of ATRA on acute promyelocytic leukemia, a type of acute myeloid leukemia, are mainly due to the induction cell differentiation [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, terpenoids II (Scheme 1a-1), dimers of the related retinal and their analogues, are a large family of naturally occurring pigments and are related to numerous physiological functions, and many of them are also fundamental chemicals widely applied in food, nutrition, cosmetics, and elsewhere. [4,9] Inspired by the functions of these natural compounds, many non-natural bioactive molecules I, such as peretinoin (NIK-333; phase III trials), [10] ALRT1550, [11] acitretin, [4] and fenretinide, [12] have been invented (Scheme 1a-2).…”
Section: Introductionmentioning
confidence: 99%